Infant feeding choices and practices of HIV-positive mothers at Lower Umfolozi District War Memorial Hospital, Empangeni, KwaZulu-Natal Province - Abusomwan, Osaigbovo Ebenezer (My University, 2012)
Introduction: KwaZulu-Natal is one of the provinces most affected by HIV/AIDS in South Africa. The estimated HIV prevalence among pregnant women attending ante-natal clinic at LUDWMH in Empangeni is high (40%). Infant feeding practices by these mothers are critical to reducing MTCT of HIV. The objectives of the study are: to describe the ante-natal infant feeding choices of a group of HIV-positive women attending the PMTCT clinic at LUDWMH; to determine the infant feeding practices of these women during the six weeks post-natal period; to determine the correlation between these mothers‟ infant feeding choices and their actual infant feeding practices six weeks after childbirth; to describe these women‟s socio-environmental conditions; and to determine the compliance of their infant feeding practices to safe infant feeding guidelines. Materials and methods: A descriptive cross-sectional study design was used. The mothers were from the predominantly poor-rural communities in Area 3 of northern KwaZulu-Natal. Data were obtained by the use of structured questionnaires which were directly administered to 395 mothers attending the PMTCT clinic six weeks after childbirth. Their ante-natal clinic records were also reviewed. Data entry was done with Microsoft Access. The data were analysed using Epi Info and Microsoft Excel. Results: The commonest ante-natal infant feeding choice was exclusive breastfeeding (78.2%) which was more than the combined number of women who chose replacement feeding (19.2%) and mixed feeding (2.5%). Majority of the mothers practiced their infant feeding choices in the six weeks post-natal period (p-value = 0.000). Expectedly, access to regular maternal income was low (36.7%; 95% CI 32.0 – 41.7). However, access to the other three individual socio-environmental resources was high [safe water (66.8%; CI 61.9 – 71.4); fuel (83%; CI 79.0 – 86.6); fridge/freezer (82.5%; CI 78.4 – 86.1)]. Approximately 61% of women had access to all three of these resources (cumulatively). Discussion and conclusions The study demonstrated that exclusive breastfeeding is the predominant infant feeding choice and practice amongst women attending LUDWMH, Empangeni in KwaZulu-Natal province. The high uptake of exclusive breastfeeding (77.7%) in the six weeks post-natal period is encouraging given the heavy burden of diarrhoeal diseases and protein-energy malnutrition with associated high mortality rates in this setting. Another encouraging finding that may help to improve prevention of MTCT of HIV was that mixed feeding was uncommon in these women. The finding that almost two-thirds of mothers who practiced replacement feeding complied with WHO/National guidelines for safe replacement feeding in this largely poor-rural setting is commendable.
Keywords: Infant Feeding